Hubungan Komunikasi Terapeutik Perawat dengan Motivasi Sembuh pada Pasien Diabetes Mellitus di Ruang Rawat Inap Rumah Sakit XX - Reno Kalidupa; Lilla Maria (Jurnal Ilmiah Kesehatan Rustida, 2021)
Nurses must have communication skills that are professional in nature and aim to cure the patient. Motivation in the patient will be important because it is related to the healing goals that will be achieved. The aim of the study was to see the relationship between nurse therapeutic communication and motivation to recover in patients who were treated in the inpatient room of the Baptis Batu Hospital. The research design used was analytic observational with cross sectional approach. This study used purposive sampling technique and the sample used was 37 respondents. The results showed that from 37 respondents, it was found that 30 respondents (81.1%) and 7 respondents had poor therapeutic communication (18.9%). From 30 respondents, 27 (73.0%) good therapeutic communication with high motivation to recover. while from 7 who got poor therapeutic communication, 6 respondents (16.2%) had low motivation. The spearman rank test results show that the values of 0.752 p-value <0.001 where p<α 0.05 Ha is accepted by Ho is rejected. Good nurse therapeutic communication shows that nurses in the inpatient room of Batu Baptis Hospital have implemented therapeutic communication techniques so that diabetes mellitus patients have the motivation to recover.